Academic ecosystem and change management effects on learning service quality in higher education - Reinhard Leonardo Paais; Nur Aedi (Indonesian Journal of Educational Development (IJED), 2026)
The increasing demand for high-quality learning services in higher education is often not matched by institutional readiness to develop supportive academic ecosystems and manage change effectively, creating a gap between student expectations and actual service quality. This study examines the effects of the academic ecosystem and change management on learning service quality at the postgraduate level in response to the growing expectation that universities function as service-oriented institutions. A quantitative survey was conducted involving all 95 postgraduate students enrolled in the Educational Administration Study Program, Faculty of Education, Universitas Pendidikan Indonesia. Given the relatively small population, a census sampling technique was employed, with all students included as respondents. Data were collected through questionnaires and analyzed using multiple linear regression after meeting the classical assumption tests. The results indicate that the academic ecosystem and change management have positive and significant effects on learning service quality, both simultaneously and partially, with a combined contribution of 49.9%. The academic ecosystem exerts a stronger influence (β = 0.479) than change management (β = 0.327). These findings suggest that strengthening academic ecosystems and implementing sustainable change management are essential for improving learning service quality and enhancing institutional competitiveness in higher education.